The effects of complex elastic band training on physical fitness components in junior female handball players - Mehrez HAMMAMI; Ryland MORGANS; Piotr ŻMIJEWSKI (Baltic Journal of Health and Physical Activity)
Introduction: The aim of this study was to examine the effects of a 10-week complex elastic band training (CEBT) program on athletic performance in junior female handball players. Methods: Participants (16.2 ± 0.5 years) were randomly assigned to an intervention group (IG; n = 16) or control group (CG; n = 14). The IG group performed CEBT twice a week during the 10-week intervention, which included eight 35-minute sessions, progressing in number of sets and band resistance for each specific exercise. The CG maintained regular in-season training. The modified T-test (T-half), squat jump (SJ), countermovement jump (CMJ), standing long jump (SLJ), repeated sprint ability (RSA), 1-RM bench press, 1-RM half squat, and force-velocity tests for both upper and lower limbs were as-sessed. Results: IG enhanced T-half [p < 0.001; d = 2.40 (large)]; jump [SJ (p = 0.001, d = 0.94 (large)), CMJ (p < 0.001, d = 1.34 (large), SLJ (p = 0.001, d = 0.91 (large))]; 3 of 4 RSA scores [p < 0.001, d = 1.59-1.70 (large)]; 1-RM bench press [p = 0.01, d = 0.68 (medium)] and 1-RM half squat [p = 0.02, d = 0.61 (medium)]; all force-velocity scores for the upper limbs [p ≤ 0.024, d = 0.60-2.30 (medium to large)]; and three of four force-velocity scores for the lower limb performance [p ≤ 0.001, d = 1.33-1.40 (large)] compared to the CG. Conclusions: CEBT performed twice a week, for 10 weeks, improves change of direction and jumping performance, RSA and muscular strength and power in junior handball athletes. There-fore, coaches and practitioners should consider utilizing CEBT as a time and resource-efficient means of improving youth handball players’ physical fitness.